Infection Characteristics of Rice Stripe Mosaic Virus in the Body of the Vector Leafhoppers - Zhao, Ping; Sun, Xiang; Li, Pan; Sun, Jiatao; Yue, Yue; Wei, Jing; Wei, Taiyun; Jia, Dongsheng (Frontiers in Microbiology, 2019)
Rice stripe mosaic virus (RSMV), a novel species of Cytorhabdovirus, is transmitted by the leafhopper Recilia dorsalis in a persistent-propagative manner. In this study, we firstly confirmed that N protein of RSMV is a component of viroplasm and virion in vector culture cells of R. dorsalis. Confocal microscopy revealed that RSMV initially accumulated in epithelial cells of the filter chamber of R. dorsalis, from where it proceeded to the visceral muscles surrounding the filter chamber. Subsequently, RSMV spread quickly throughout the suspensory ligament to the salivary glands. Meanwhile, RSMV spread from the filter chamber to midgut, hindgut, oesophagus, hemolymph and central nervous system. We further observed that RSMV particles displayed as non-enveloped form when propagating in cytoplasm of different tissues, and became enveloped when spread within insect body by electron microscopy. Additionally, we found that the leafhopper Nephotettix virescens was also able to acquire and transmit RSMV. These results clarified the infection characteristics of RSMV in its leafhopper vectors, which will help guide the formulation of RSMV prevention and control strategies.